Strengthening Religious And Social Values Through Fardu Kifayah Training: An ABCD-Based Community Empowerment Study - Lubis, Arbonas; Al Farizi, Saddam; Raihan Lubis, Habib; Cahyadi, Bagus; Ananda Sugma, Tri (ASSUNNAH PRESS, 2025)
This study examines strengthening religious and social values through fardu kifayah training using Participatory Action Research (PAR) integrated with Asset-Based Community Development (ABCD) principles in Tangga Batu Village, a minority Muslim community in Toba Regency, North Sumatra. Employing descriptive qualitative methodology within a community service framework, this program implemented four cyclical PAR stages: Planning, Action, Observation, and Reflection over 14 days (March 4-17, 2025). Data collection involved participatory observation, in-depth interviews with 25 community members, and comprehensive documentation. The study engaged 45 participants, including youth (60%), religious leaders (20%), and community members (20%). Findings reveal significant community understanding and skills enhancement, particularly among younger generations, in independently performing fardu kifayah rituals. Active involvement of educational institutions and religious figures strengthened the community's collective awareness and social solidarity. The study concludes that the ABCD approach effectively identifies and optimizes local assets, enabling the development of participatory and sustainable religious-based empowerment models in multicultural settings.